OPTIMALISASI LITERASI REMAJA MENGENAI GLOBAL WARMING MELALUI INOVASI MEDIA TAS EDUKASI KESEHATAN - Ridha Mardiyani; Lidia Hastuti; Wien Fitrien (Jurnal LENTERA, 2026)
Background: Global warming is driven by increasing greenhouse gas (GHG) emissions, one of which originates from the widespread use of single-use polyethylene plastic bags that are difficult to decompose and release harmful emissions when burned. These environmental changes contribute to an increased risk of tropical infectious diseases, respiratory disorders, and waterborne diseases. Therefore, raising public awareness to adopt reusable environmentally friendly bags as an alternative to single-use plastic bags is essential. Objective: This community engagement program aimed to train students to develop Health Education Totebag as an educational medium to promote plastic bag reduction campaigns while enhancing awareness of healthy lifestyles. Methods: The program involved 11 students from eight Health Vocational High Schools in Pontianak and Kubu Raya. The workshop began with educational sessions on global warming and waste management delivered by the Environmental Agency, followed by hands-on training in designing educational posters using Artificial Intelligence (AI). The completed poster designs were printed on canvas tote bags to serve as environmental education media. The program was evaluated by assessing the quality of the poster designs based on theme relevance, creativity, clarity of educational messages, and visual quality. Results: Participants demonstrated improved skills in designing educational posters using AI-based technology. The program also strengthened students' entrepreneurial competencies by introducing the potential commercialization of environmentally friendly educational tote bags. Conclusion: The Health Education Totebag is an effective educational medium and an environmentally friendly alternative to single-use plastic bags. It supports plastic reduction policies while promoting public awareness of sustainable Green Living practices. Keywords: Educational tote bag, Health, School Health Unit (UKS), Eco-friendly